Response from F R Khan, S M R Kazmi, H K Siddiqui, et al. (J Pak Med Assoc. 2023; 73: 1275-1279) Prosthetic complications with dental implants: A bibliometric analysis of 20 top cited articles - Farhan Raza Khan; Syed Murtaza Raza Kazmi; Humayun Kaleem Siddiqui; Ayesha Aziz (Journal of the Pakistan Medical Association, 2023)
dental implants: a bibliometric analysis of 20 top cited articles. J Pak Med Assoc. PMID: 37427629.”1was published in June 2023. We believe that the reader has mixed up this paper with an earlier paper of ours, titled “A bibliometric analysis of the studies on dental implant failure. J Pak Med Assoc. PMID: 35202375.2 Dental implants have two types of failures: surgical (related to implant fixture, its placement techniques and bone biology etc.) and prosthetic (related to implant prosthesis, crown, abutment, other components, or technical issues arising from laboratory made implant prosthesis). The former paper was about identifying the top-cited publications on the surgical failures of implants whereas the latter bibliometrics related to the implant prosthetic complications. Regarding methodology of bibliometrics, the search terms we adopted for the first paper was “dental implant failure” whereas for the second paper, we employed “Prosthetic complication in dental implant” without using any Boolean operator. These key terms were searched in the abstracts using Web of Science, Google Scholar, and other electronic sources published in English language upto June 2021. We employed the option of “cited reference search” for ascertaining the number of citations. To review and synthesise the data, multiple parameters were explored. These included authors, journal, citation count, citation density, keywords and study design, and geographic and institutional affiliation of the first or corresponding authors. The country of literature emergence was determined by the address of the corresponding author. The details of methodology are already shared in the above-mentioned papers. Another important observation made by the reader was that the table 2 and table 3 displayed the same information that has already been shared in table 1. So why was it done? And that too in both the papers. The answer to this question is that although table 1 in both the papers displayed the primary bibliometric data but to stratify the data, based on author, institution, and the journal, table 2 was composed and to emphasize the study designs table 3 was made. That helped us to identify that there is just one clinical trial among top 30 cited papers on dental implant failures and more alarmingly, no randomized controlled trials in the list of top 20 cited papers on the implant prosthetic failures. Thus, table 2 and table 3 represented the subset of the data.